Proteins associated with rabbit reticulocyte mRNA caps during translation as investigated by photocrosslinking. - Greenberg, J R (1988)
This laboratory previously detected by UV crosslinking a number of proteins associated with cytoplasmic mRNA in mammalian cells, and the data suggested that they are involved in translation. To find out which proteins are associated with caps we made use of reticulocyte mRNA specifically labeled in the cap with 32P together with a cell-free translation system and UV crosslinking. Approximately 8 bands corresponding to proteins crosslinked to the cap itself have been detected by polyacrylamide gel electrophoresis after UV crosslinking and digestion with RNases or tobacco pyrophosphatase. All but one were specific for methylated caps. One was similar in size and partial peptide map to a cap-binding protein, CBP I, previously identified in other laboratories, and most of the others corresponded to proteins previously known to be associated with mRNA but not known to be associated with caps. The results suggest that most mRNA-associated proteins are associated with caps or poly(A). Also, the number of cap-associated proteins may be greater than previously suspected.